Science of the Total Environment - Trina Rytwinski; Steven J. Cooke; Jessica J. Taylor; Dominique G. Roche; Paul A. Smith; Greg W. Mitchell; Karen E. Smokorowski; KentA.Prio; Joseph R. Bennett (Elsevier, 2025)
Evidence-based decision-making often depends on some form of a synthesis of previous ﬁndings. There is growing recognition that systematic reviews, which incorporate a critical appraisal of evidence, are the gold standard synthesis method in applied environmental science. Yet, on a daily basis, environmental practitioners and decision-makers are forced to act even if the evidence base to guide them is insufﬁcient. For example, it is not uncommon for a systematic review to conclude that an evidence base is large but of low reliability. There are also instances where the evidence base is sparse (e.g., one or two empirical studies on a particular taxa or intervention), and no additional evidence arises from a systematic review. In some cases, the systematic review highlights considerable variability in the outcomes of primary studies, which in turn generates ambiguity (e.g., potentially context speciﬁc). When the environmental evidence base is ambiguous, biased, or lacking of new information, practitioners must still make management decisions. Waiting for new, higher validity research to be conducted is often unrealistic as many decisions are urgent. Here, we identify the circumstances that can lead to ambiguity, bias, and the absence of additional evidence arising from systematic reviews and provide practical guidance to resolve or handle these scenarios when encountered. Our perspective attempts to highlight that, with evidence synthesis, there may be a need to balance the spirit of evidence-based decision-making and the practical reality that management and conservation decisions and action is often time sensitive.